QBD Approach to Predict the in-vivo Performance Based on in-vitro Results using Mucuna pruriens Seed Mucilage as a Novel Tablet Dosage Form Excipient and Dicofenac Sodium as Model drug Candidate - Deokar, Gitanjali Sambhajirao; Kakulte, Harshada Dnyandeo; Kshirsagar, Sanjay Jayprakash; Waghchoure, Dnyaneshwar Ramnath (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Aim of the present study was to put forth certain modifications in Quality by design approach to predict the in-auto performance of dosage form based on in-vivo performance parameter simulation using in-vitro experimentations. Materials and Methods: One factor design was used with prime focus on impact of Mucuna pruriens seed mucilage as excipient on dosage form functionality and applicability. During product development stage, apart from manufacturing variables other impacting parameters considered were GI pH, alterations in body temperature and GI motility. Factors considered were simulated pH, Temperature and RPM (Rotations per minutes) variations. Process flow worksheet was developed. QTPP (Quality target product profile) and CQA (Critical Quality Attributes) data was generated. Results: Risk assessment and Ishikawa diagram (Cause and effect analysis) were found to be helpful to generate the results predicting in vivo performance of dosage from. The process capability indices helped for judging product/process performance. The study design could be helpful to analyze the alterations in in-vivo performance based on excipient behavior in simulated conditions tested in-vitro. Conclusion: The present research work has successfully used Quality by design approach to predict the in-vivo performance of Tablet dosage form based on in-vitro data simulation. It can be concluded that study design with more number of simulating variables could be helpful pattern to come up with in-vivo performance predictions.
Keywords: Mucuna pruriens; Seed polymer; Excipient; QbD perspective; Process capability study; Ishikawa diagram; QTPP; CQA